The dose-response effect of aerobic exercise on inflammation in colon cancer survivors - Brown, Justin C.; Compton, Stephanie L.E.; Meyerhardt, Jeffrey A.; Spielmann, Guillaume; Yang, Shengping (Frontiers in Oncology, 2023)
Background: Physical activity after surgical resection for colon cancer is associated with significantly longer disease-free survival. Inflammation is hypothesized to mediate the association between physical activity and disease-free survival in colon cancer.In this exploratory analysis of a randomized dose-response trial, 39 colon cancer survivors who completed standard therapy were stratified by cancer stage and randomized in a 1:1:1 ratio to one of three treatment groups for 24 weeks of usual-care control, 150 min/wk of moderate-intensity aerobic exercise (low-dose), or 300 min/wk of moderate-intensity aerobic exercise (high-dose). Inflammation outcomes included high-sensitivity C-reactive protein (hs-CRP), interleukin-6 (IL6), and soluble tumor necrosis factor-alpha receptor 2 (sTNFaR2). Mixed models for repeated measures were used to test the hypothesis that exercise was associated with dose-response reductions in inflammation; exploratory analyses examined treatment effects by cancer stage.In the overall population, aerobic exercise was not associated with dose-response reductions in hs-CRP, IL6, or sTNFαR2. Cancer stage modified the association between randomized group and hs-CRP (P=0.022) and IL6 (P<0.001) but not sTNFαR2 (P=0.39). In stage I-II disease, compared to control, exercise was not associated with inflammation outcomes.In stage III disease, compared to control, low-dose exercise reduced hs-CRP: −35.4% (95% CI: −70.1, −0.7) and IL6: −29.6% (95% CI: −58.4, −0.8) but not sTNFαR2: 2.7% (95% CI: sTNFαR2: −15.7, 21.1); high-dose exercise was not associated with inflammation outcomes in stage III disease.This exploratory analysis offers preliminary data to support the hypothesis that inflammation may mediate the association between physical activity and disease-free survival in colon cancer.